42=3(2-3n)-6

Simple and best practice solution for 42=3(2-3n)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42=3(2-3n)-6 equation:


Simplifying
42 = 3(2 + -3n) + -6
42 = (2 * 3 + -3n * 3) + -6
42 = (6 + -9n) + -6

Reorder the terms:
42 = 6 + -6 + -9n

Combine like terms: 6 + -6 = 0
42 = 0 + -9n
42 = -9n

Solving
42 = -9n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '9n' to each side of the equation.
42 + 9n = -9n + 9n

Combine like terms: -9n + 9n = 0
42 + 9n = 0

Add '-42' to each side of the equation.
42 + -42 + 9n = 0 + -42

Combine like terms: 42 + -42 = 0
0 + 9n = 0 + -42
9n = 0 + -42

Combine like terms: 0 + -42 = -42
9n = -42

Divide each side by '9'.
n = -4.666666667

Simplifying
n = -4.666666667

See similar equations:

| -19=3(7+3n)+8(8n-5) | | 180=111-u | | -12+19/-7= | | -12+-42/-7= | | 60x^2-20x+1=0 | | 84=2w+2L-3 | | 15y-11y=20 | | -12+-126/-7= | | x^2+(x*y)=120 | | 84+3x=1x | | -9u-5+6=19 | | -12+h/7=6 | | -a+5+6a=1+5a+3 | | -12+h/7= | | 8x+4(2-3x)=36-6x | | (4x-3)+3(3x+6)=5x-1 | | 4x^3-33x^2-30x=0 | | 2x+17+3x-4=180 | | 32=2x+14 | | 0.625=-0.50x | | 88+1.5h=94+2h | | 85=3(x-1)+8x | | -5(k-1)-(-6k+1)=9 | | 7a^2+49a+60=0 | | (sin(x))*2=116 | | 1x+-7=2x+-6 | | (sin(x))2=116 | | 4x^3-33x-30x=0 | | -3(2y-2)-y=-2(y-2) | | 4v-(6v+8)=8v-38 | | 88+1.5h=94-2h | | 9(3x+12x)= |

Equations solver categories